2021
DOI: 10.3847/1538-4357/abda51
|View full text |Cite
|
Sign up to set email alerts
|

LOFAR Observations of a Jet-driven Piston Shock in the Low Solar Corona

Abstract: The Sun produces highly dynamic and eruptive events that can drive shocks through the corona. These shocks can accelerate electrons, which result in plasma emission in the form of a type II radio burst. Despite the large number of type II radio burst observations, the precise origin of coronal shocks is still subject to investigation. Here, we present a well-observed solar eruptive event that occurred on 2015 October 16, focusing on a jet observed in the extreme ultraviolet by the Atmospheric Imaging Assembly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…A similar conclusion for five events observed in the 164−435 MHz range was reached by Maia et al (2000). The coronal shock radio sources may occur in front of an erupting flux rope (Bain et al 2012;Zimovets et al 2012;, above expanding soft X-ray loops (e.g., Klein et al 1999;Dauphin et al 2006), in association with an erupting jet during the progression of a CME (e.g., Zucca et al 2014a;Maguire et al 2021), in front of an EUV bubble in both radial and lateral directions (Kouloumvakos et al 2014) or ahead of a CME that was deflected in the low corona (Pick et al 2016).…”
Section: Introductionsupporting
confidence: 61%
“…A similar conclusion for five events observed in the 164−435 MHz range was reached by Maia et al (2000). The coronal shock radio sources may occur in front of an erupting flux rope (Bain et al 2012;Zimovets et al 2012;, above expanding soft X-ray loops (e.g., Klein et al 1999;Dauphin et al 2006), in association with an erupting jet during the progression of a CME (e.g., Zucca et al 2014a;Maguire et al 2021), in front of an EUV bubble in both radial and lateral directions (Kouloumvakos et al 2014) or ahead of a CME that was deflected in the low corona (Pick et al 2016).…”
Section: Introductionsupporting
confidence: 61%
“…Note that in the case of type II bursts, reports indicate that the centroids of F-and H-components at any given observing frequency are nearly cospatial (Zucca et al 2018). So we can consider the corresponding emission to be generated in the same location, although there could be an apparent shift in the observed position of particularly the F-component due to propagation effects (Maguire et al 2021). Moving further, depolarization as the cause of low dcp in the case of F-component O mode applies mostly to type I bursts only (see, e.g., Melrose 2017).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Recently, Shen et al (2018a) firstly reported that single-pulsed EUV waves can be directly launched by coronal jets in coronal loops. Such an excitation mechanism is similar to the generation of piston shocks in a one-dimensional tube, in which the jet acted as the driver of the wave train that can propagate faster than its driver (Warmuth 2015;Ying et al 2018;Maguire et al 2021). According to the piston shock scenario, our present QFP wave train could be driven by the jet ejection, in which two QFP wave fronts might related to unresolved discrete fine structures consisting of the jet body.…”
Section: Discussionmentioning
confidence: 83%